Politisk psykologi – De næste skridt - Petersen, Michael Bang; Aarøe, Lene (Politik, 2014)
The eld of political psychology is steadily growing. But how do researchers most fruitfully contribute to the increasing stock of knowledge about the psychological underpinnings of political behavior? In this article, we outline the scienti c ideals of political psychology and we point to the most recent key theoretical and methodical innovations in the eld. Our core message is that political psychology by nature is an interdis- ciplinary eld. e better the research re ects this interdisciplinary nature, the more powerful it will be.